New Inscriptions from Nikaia XVII - Hüseyin Sami ÖZTÜRK; Ali Oğuz BOZKURT (Phaselis: Disiplinlerarası Akdeniz Araştırmaları Dergisi)
This article introduces a total of six new inscriptions discovered in the Central, Söğüt, and Yenipazar districts of Bilecik Province. In antiquity, these districts were part of the territorium of Nicaea. These funerary inscriptions are important in that they introduce us to new names that were previously unknown in the region, and they are dated mainly to the IInd-IIIrd centuries AD, the Roman Imperial period. A number of names previously documented in Anatolia or Greece were documented for the first time in the territory of Nicaea. Among these are Antandros and Thetis. It is particularly noteworthy that the name Thetis, which is not very common, appears here. Therefore, this article contains important data on the demographic structure and onomastics of the region.